Observer variabilities for the diagnosis of coronary artery disease using anatomical and functional testing: the impact of certification - Korosoglou, Grigorios; Abanador-Kamper, Nadine; Tesche, Christian; Renker, Matthias; André, Florian; Weichsel, Loris; Hell, Michaela; Bönner, Florian; Cramer, Mareike; Kelle, Sebastian; Schulz-Menger, Jeanette; Fehske, Wolfgang; et al. (Clinical research in cardiology, 2025)
To compare the reproducibility in reporting of coronary computed tomography angiography (CCTA) or cardiovascular magnetic resonance imaging (CMR) by certified readers for CCTA and CMR by the German Society of Cardiology (DGK) versus that by non-certified readers.